The Significance of Linguistic Approach to Certain Lexemas in "Devoni Lug'otit Turk" - Musaуev Isomiddin Saidovich (International Journal on Orange Technologies, 2022)
By the beginning of the 21st century, linguistics and cultural studies have become one of the leading directions in world linguistics. As stated in many studies, linguistics is a science that studies language as a cultural phenomenon, and its subject is language and culture in mutual relationship. Linguistic studies in Uzbek linguistics began to appear in the last two decades. Linguistics studies the culture of the people, which is reflected and reinforced in language and discourse. First of all, he researches myths, legends, customs, traditions, customs, customs, and symbols of a certain culture. These concepts are related to culture, and they are reinforced in the language in the form of household and food behavior. The article talks about the linguistic and cultural characteristics of some lexical units in Mahmud Koshgari's Devonu dictionary-Turkish work.